Implementasi Peraturan Daerah Tentang Ketertiban Umum Dalam Perspektif Siyasah Tanfidziyah Di Kabupaten Lampung Utara - Hidayah, Sri Wulan Nur; Karini, Eti; Rahma, Nur (UNIB Press, 2026)
This study examines the implementation of Article 11 Paragraph 1 Letter a of North Lampung Regency Regional Regulation Number 4 of 2022 on Public Order through the lens of Siyasah Tanfidziyah. A descriptive-analytical qualitative approach was employed through field research and empirical juridical methods, with data gathered via in-depth interviews with Civil Service Police Unit (Satpol PP) officers, vehicle owners, and open-truck drivers, complemented by direct field observation. The findings reveal that normatively, the regulation is aligned with the principles of hifzh al-nafs, Maslahah Mursalah, and maqashid al-syariah, qualifying it as a legitimate and accountable policy issued by Ulil Amri. Field realities, however, indicate that implementation has yet to reach its optimal level, constrained by five key inhibiting factors: limited socialization in remote areas, community dependence on open-bed vehicles as the primary means of transporting agricultural produce and materials, weak deterrent effect of sanctions, narrow patrol coverage, and a complaint mechanism that has not been adequately publicized. This study advances a new proposition that the effectiveness of maqashid al-syariah-based policy cannot rely solely on the quality of its legal substance, but equally requires genuine commitment and consistency from enforcement officers in carrying out the Siyasah Tanfidziyah function. Equitable socialization, consistent enforcement, and expanded supervisory coverage are recommended as key measures to realize public welfare in agrarian regions.